Biofilms, bubbles and boundary layers – A new approach to understanding cellulolysis in anaerobic and ruminant digestion. (1st November 2016) - Mason, P. Michael; Stuckey, David C.
Abstract: Anaerobic digestion of plant biomass to hydrocarbons could play a major part in meeting the needs of a modern low carbon society, but the cost reductions needed to make it an economically viable technology have been slower to arrive than in other renewable technologies. This is notwithstanding the observation that ruminants carry out the rate limiting hydrolysis step up to 30 times faster than an AD plant, and that bio-mimicry of ruminants could be an important source of innovation. This paper examines a number of factors which may, by focusing emphasis on the physical and chemical environment within cellulolytic biofilms, help accelerate development in the arena. It examines the process of cellulolysis from the perspective of a bacterium attached within a biofilm to a piece of insoluble cellulosic substrate to illustrate the extent of chemical heterogeneity that exists in the film, and between the film and the supernatant, and how this might control the rate of cellulolysis. It suggests several strategies used by ruminants to manage this heterogeneity that may be significant contributors to their effectiveness, and could provide a useful guide to more effective anaerobic digestion. Graphical abstract: Highlights: Anaerobic digestion (AD) could be important in global renewables but too expensive. Bio-mimicry of ruminant digestion could accelerate anaerobic digestion up to 30 times. AD of biomass rate limited by cellulolysis carried out by bacteria in biofilms. Biofilm environment very different from bulk liquid and this controls cellulolysis. Understanding biofilm environment crucial to rate and cost of anaerobic digestion.